2020
DOI: 10.1002/cne.25013
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐brain efferent and afferent connectivity of mouse ventral tegmental area melanocortin‐3 receptor neurons

Abstract: The mesolimbic dopamine (DA) system is involved in the regulation of multiple behaviors, including feeding, and evidence demonstrates that the melanocortin system can act on the mesolimbic DA system to control feeding and other behaviors. The melanocortin‐3 receptor (MC3R) is an important component of the melanocortin system, but its overall role is poorly understood. Because MC3Rs are highly expressed in the ventral tegmental area (VTA) and are likely to be the key interaction point between the melanocortin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…It also appears unlikely that differences in the circuit connectivity of VTA MC3R neurons would mediate these effects, as we have recently shown that male and female VTA MC3R neurons do not differ in their efferent projections or their afferent inputs (Dunigan et al, 2020). One potential explanation for the differences observed here is that there could be sex differences in the specific neurotransmitters or combinations of transmitters released from VTA MC3R neurons.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It also appears unlikely that differences in the circuit connectivity of VTA MC3R neurons would mediate these effects, as we have recently shown that male and female VTA MC3R neurons do not differ in their efferent projections or their afferent inputs (Dunigan et al, 2020). One potential explanation for the differences observed here is that there could be sex differences in the specific neurotransmitters or combinations of transmitters released from VTA MC3R neurons.…”
Section: Discussionmentioning
confidence: 58%
“…It also appears unlikely that differences in the circuit connectivity of VTA MC3R neurons would mediate these effects, as we have recently shown that male and female VTA MC3R neurons do not differ in their efferent projections or their afferent inputs (Dunigan et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have identified the involvement of MC3Rs and MC4Rs in reward circuits. Antagonists acting on MC3Rs and MC4Rs result in alterations in reward behaviors and locomotor activity (de Vrind et al, 2021;Dunigan et al, 2021a). A reward is derived from sex behaviors and regions such as the NAc, CPu, and the VTA are involved in the reward circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Hosp et al, 2011 identified a projection between the VTA and Mop (M1), showing the contribution of dopaminergic connections originating from the VTA in motor skill learning. Other studies showed that the VTA serves as a hub of divergence with projections to SI, LC, DR, RT (nRT) ( Dunigan et al, 2021 ), and bfd ( Aransay et al, 2015 ), all critical for the information processing in the whisker system. Finally, the novel discoveries along the neuromodulatory circuits and their integration with nuclei in the whisker system are not limited to the dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%